Solve the following IVP using Laplace Transform y′′+3y′+2y=e^(-t), y(0)=0 y′(0)=0

Solve the following IVP using Laplace Transform y′′+3y′+2y=e^(-t), y(0)=0 y′(0)=0

Question
Laplace transform
asked 2021-03-09
Solve the following IVP using Laplace Transform
\(y′′+3y′+2y=e^(-t), y(0)=0 y′(0)=0\)

Answers (1)

2021-03-10
Step 1
We have to solve given IVP using Laplace transform.
Step 2
We have given
\(y′′+3y′+2y=e^(-t), y(0)=0 y′(0)=0\)
Taking Laplace transform on given differential equation
\(\displaystyle{L}{\left({y}{''}+{3}{y}′+{2}{y}\right)}={L}{\left({e}^{{-{t}}}\right)}\)
\(\displaystyle{L}{\left({y}{''}\right)}+{3}{L}{\left({y}′\right)}+{2}{L}{\left({y}\right)}=\frac{1}{{{s}+{1}}}\ldots{\left({i}\right)}\)
We are using here
\(\displaystyle{L}{\left({y}{''}\right)}={s}^{2}{Y}{\left({s}\right)}-{s}{y}{\left({0}\right)}-{y}′{\left({0}\right)},{L}{\left({y}′\right)}={s}{Y}{\left({s}\right)}-{y}{\left({0}\right)}\ \text{ and }\ {L}{\left({e}^{{-{t}}}\right)}=\frac{1}{{{s}+{1}}}\)
where \(L(y)=Y(s)\)
Then from equation (i) we get,
\(\displaystyle{s}^{2}{Y}{\left({s}\right)}-{s}{y}{\left({0}\right)}-{y}′{\left({0}\right)}+{3}{\left({s}{Y}{\left({s}\right)}-{y}{\left({0}\right)}\right)}+{2}{Y}{\left({s}\right)}=\frac{1}{{{s}+{1}}}\)
\(\displaystyle{s}^{2}{Y}{\left({s}\right)}+{3}{s}{Y}{\left({s}\right)}+{2}{Y}{\left({s}\right)}=\frac{1}{{{s}+{1}}}\)
\(\displaystyle{\left({s}^{2}+{3}{s}+{2}\right)}{Y}{\left({s}\right)}=\frac{1}{{{s}+{1}}}\)
\(\displaystyle{\left({s}{\left({s}+{1}\right)}+{2}{\left({s}+{1}\right)}\right)}{Y}{\left({s}\right)}=\frac{1}{{{s}+{1}}}\)
\(\displaystyle{\left({s}+{1}\right)}{\left({s}+{2}\right)}=\frac{1}{{{s}+{1}}}\)
\(\displaystyle{Y}{\left({s}\right)}=\frac{1}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}\ldots{\left({i}{i}\right)}\)
Now
\(\displaystyle\frac{1}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}=\frac{A}{{{s}+{1}}}+\frac{B}{{\left({s}+{1}\right)}^{2}}+\frac{C}{{{s}+{2}}}\)
\(\displaystyle\frac{1}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}=\frac{{{A}{\left({s}+{1}\right)}{\left({s}+{2}\right)}+{B}{\left({s}+{2}\right)}+{C}{\left({s}+{1}\right)}^{2}}}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}\)
\(\displaystyle{1}={A}{\left({s}+{1}\right)}{\left({s}+{2}\right)}+{B}{\left({s}+{2}\right)}+{C}{\left({s}+{1}\right)}^{2}\)
Put s=-1 we get
B=1
Put s=-2 we get
C=1
Comparing s^2 coefficent we get
\(A+C=0\)
\(\displaystyle\Rightarrow{A}=-{1}\)
So,
\(\displaystyle\frac{1}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}=-\frac{1}{{{s}+{1}}}+\frac{1}{{\left({s}+{1}\right)}^{2}}+\frac{1}{{{s}+{2}}}\)
Step 3
Now, from equation (ii)
\(\displaystyle{Y}{\left({s}\right)}=\frac{1}{{{\left({s}+{1}\right)}^{2}{\left({s}+{2}\right)}}}\)
\(\displaystyle\Rightarrow{Y}{\left({s}\right)}=-\frac{1}{{{s}+{1}}}+\frac{1}{{\left({s}+{1}\right)}^{2}}+\frac{1}{{{s}+{2}}}\)
Taking Laplace inverse on both sides we get
\(\displaystyle{L}^{ -{{1}}}{\left({Y}{\left({s}\right)}\right)}={L}^{ -{{1}}}{\left(\frac{{-{1}}}{{{s}+{1}}}\right)}+{L}^{ -{{1}}}{\left(\frac{1}{{\left({s}+{1}\right)}^{2}}\right)}+{L}^{ -{{1}}}{\left(\frac{1}{{{s}+{2}}}\right)}\)
\(\displaystyle\Rightarrow{y}{\left({t}\right)}=-{e}^{{-{t}}}+{t}{e}^{{-{t}}}+{e}^{{-{2}{t}}}\)
This is the solution of differential equation.
0

Relevant Questions

asked 2021-01-13

Find Y(t) using Laplace transform.
\(\displaystyle{y}{''}+{2}{y}'+{5}{y}={e}^{{-{T}}} \sin{{T}}\)
\(y(0)=0 , y'(0)=1\)

asked 2020-11-01
Solve the following IVP using Laplace Transform
\(y'-2y =1-t , y(0)=4\)
asked 2020-11-14
Use the Laplace transform to solve the given initial-value problem
\(y′′+2y′+y =\delta(t-4)\)
\(y(0)=0\)
\(y′(0)=0\)
asked 2021-01-30
Use Laplace transform to find the solution of the IVP
\(2y'+y=0 , y(0)=-3\)
a) \(f{{\left({t}\right)}}={3}{e}^{{-{2}{t}}}\)
b)\(f{{\left({t}\right)}}={3}{e}^{{\frac{t}{{2}}}}\)
c)\(f{{\left({t}\right)}}={6}{e}^{{{2}{t}}}
d) \(f{{\left({t}\right)}}={3}{e}^{{-\frac{t}{{2}}}}\)
asked 2020-12-21
Solve the IVP with Laplace Transform:
\(\begin{cases} y"+4y'+4y=(3+t)e^{-2t} \\ y(0)=2 \\ y'(0)=5 \end{cases}\)
asked 2021-02-19
Use Laplace transform to solve the following initial-value problem
\(y"+2y'+y=0\)
\(y(0)=1, y'(0)=1\)
a) \displaystyle{e}^{{-{t}}}+{t}{e}^{{-{t}}}\)
b) \displaystyle{e}^{t}+{2}{t}{e}^{t}\)
c) \displaystyle{e}^{{-{t}}}+{2}{t}{e}^{t}\)
d) \displaystyle{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
e) \displaystyle{2}{e}^{{-{t}}}+{2}{t}{e}^{{-{t}}}\)
f) Non of the above
asked 2020-12-01
Using Laplace Transform , solve the following differential equation
\({y}\text{}-{4}{y}={e}^{{-{3}{t}}},{y}{\left({0}\right)}={0},{y}'{\left({0}\right)}={2}\)
a) \(\frac{14}{{20}}{e}^{{{2}{t}}}-\frac{5}{{30}}{e}^{{-{2}{t}}}-\frac{9}{{30}}{e}^{{-{6}{t}}}\)
b) \(\frac{11}{{20}}{e}^{{{2}{t}}}-\frac{51}{{20}}{e}^{{-{2}{t}}}-\frac{4}{{20}}{e}^{{-{3}{t}}}\)
c) \(\frac{14}{{15}}{e}^{{{2}{t}}}-\frac{5}{{10}}{e}^{{-{2}{t}}}-\frac{9}{{20}}{e}^{{-{3}{t}}}\)
d) \(\frac{14}{{20}}{e}^{{{2}{t}}}+\frac{5}{{20}}{e}^{{-{2}{t}}}-\frac{9}{{20}}{e}^{{-{3}{t}}}\)
asked 2020-12-17
Find the Laplace transform Y(s), of the solution of the IVP
\(y"+3y'+2y=\cos(2t)\)
\(y(0)=0\)
\(y'(0)=1\)
Do not solve the IVP
asked 2021-01-13

The function
\(\begin{cases}t & 0\leq t<1\\ e^t & t\geq1 \end{cases}\)
has the following Laplace transform,
\(L(f(t))=\int_0^1te^{-st}dt+\int_1^\infty e^{-(s+1)t}dt\)
True or False

asked 2021-02-19
Solve the differential equation using Laplace transform of
\(y''-3y'+2y=e^{3t}\)
when y(0)=0 and y'(0)=0
...